Effects of Attentional Focus on Repetitions-to-Failure & Motor Unit Excitation During Submaximal Bench Press Performance - Connor Collum; Ronald Snarr; Nicholas Siekirk; Samuel Wilson (International Universities Strength and Conditioning Association, 2021)
Attentional focus strategies refer to the use of cues or other stimuli to enhance an individual's concentration for the purpose of improving performance within a given task. PURPOSE: To examine the effects of an internal (INT), external proximal (EPr), and external distal (ED) method of attentional focus on motor unit excitation and repetitions-to-failure (RTF) during submaximal bench press performance. METHODS: Twenty-five recreationally-active males and females completed a one-repetition maximum (1RM) bench press test, followed by three days of submaximal testing at 85% 1RM to muscular failure. For each submaximal day, a specific attentional focus strategy was given by auditory cues (i.e., INT, EPr, ED) with the individual instructed to focus solely on the cue. Motor unit recruitment of the anterior deltoid, pectoralis major, and triceps brachii was measured, via electromyography (EMG), for each repetition for all interventions. RESULTS: Results indicated no differences for motor unit excitation (chest: p=0.59; triceps: p=0.50; deltoids: p=0.17) or RTF (p=0.89) among the three conditions. The INT cue, as compared to EPr and ED, elicited a ~7-10% average increase in pectoralis major motor unit excitation, despite an average of one less repetition. All effect sizes were deemed small or trivial, except for RTF between INT and ED which elicited a moderate effect size (ES=0.55). CONCLUSIONS: These findings support previous literature demonstrating increases in motor unit excitation with an internal attentional focus. However, this strategy may place a greater demand on the targeted musculature to complete a given task; thus, decreasing performance.